Eritrea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper examines the impact of relief and reconstruction expenditures in Eritrea on the fiscal profile. The paper discusses the principle categories of extraordinary expenditures, which the authorities have undertaken during 1993-96 for relief and reconstruction purposes. It analyzes developments and reforms in the financial system. The paper highlights that Eritrea's financial system has undergone considerable reform through the mid-1990s, but remains rudimentary and concentrated, and is still largely owned and controlled by the state.